Air pollution and hospital admissions for respiratory diseases in the subequatorial Amazon: a time series approach Poluição do ar e admissões hospitalares por doenças respiratórias na Amazônia subequatorial: abordagem de séries temporais - Eliane Ignotti; Sandra de Souza Hacon; Washington Leite Junger; Dennys Mourão; Karla Longo; Saulo Freitas; Paulo Artaxo; Antônio Carlos Monteiro Ponce de Leon (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The objective of the study is to evaluate the effect of the daily variation in concentrations of fine particulate matter (diameter less than 2.5µm - PM2.5) resulting from the burning of biomass on the daily number of hospitalizations of children and elderly people for respiratory diseases, in Alta Floresta and Tangará da Serra in the Brazilian Amazon in 2005. This is an ecological time series study that uses data on daily number of hospitalizations of children and the elderly for respiratory diseases, and estimated concentration of PM2.5. In Alta Floresta, the percentage increases in the relative risk (%RR) of hospitalization for respiratory diseases in children were significant for the whole year and for the dry season with 3-4 day lags. In the dry season these measurements reach 6% (95%CI: 1.4-10.8). The associations were sig-nificant for moving averages of 3-5 days. The %RR for the elderly was significant for the current day of the drought, with a 6.8% increase (95%CI: 0.5-13.5) for each additional 10µg/m3 of PM2.5. No as-sociations were verified for Tangara da Serra. The PM2.5 from the burning of biomass increased hospitalizations for respiratory diseases in children and the elderly. Avaliar o efeito da variação diária nas concentrações de PM2.5 da queima de biomassa sobre o número diário de hospitalizações de crianças e idosos por doenças respiratórias, em Alta Floresta e Tangará da Serra, Amazônia brasileira, em 2005. Estudo ecológico de séries temporais de hospitalizações por doenças respiratórias de crianças e de idosos, estimativas de concentrações diárias de PM2.5, variáveis meteorológicas e de calendário. Para Alta Floresta os aumentos percentuais do risco relativo (%RR) de internações por doenças respiratórias em crianças foram significantes para o ano todo e para o período de seca, com defasagens de 3-4 dias. No período de seca o incremento é de 6% (IC95%: 1,4-10,8). Para médias móveis de 3-5 dias as associações mostraram-se significantes. O %RR para idosos foram significantes para o dia corrente na seca com 6,8% (IC95%: 0,5-13,5) de incremento para aumento de 10µg/m³ de PM2.5. Não foram verificadas associações para Tangara da Serra. As emissões de PM2.5 pela queima de biomassa na Amazônia aumentaram as hospitalizações por doenças respiratórias de crianças e idosos.